Teaching Object-Oriented Programming with Games - Lu Yan (2009 Sixth International Conference on Information Technology: New Generations, 2009)
First-year students in CS/IT curriculum are often overwhelmed by the introduction to programming module, which is a mandatory component for the whole study program. In this paper, we discuss the difficulties students may encounter in this module and propose a novel approach to teaching programming to new programmer with games. We reflect on our experiences on making the programming module friendly and improving the success rate among new programmers. We present our learning theory, teaching methodology and assistive software with technical details.